Peran start up untuk pengembangan kewirausahaan mahasiswa pasca pandemi covid 19 di Indonesia - Okky Ferdiansyah; Erwin Permana (Jurnal Riset Pendidikan Ekonomi, 2022)
Start-ups have become an important part of the business development of young entrepreneurs. There is enough evidence to show that young entrepreneurs are successful with the start-ups they build. The Covid-19 pandemic has caused massive digital use in life. This reality is increasingly providing greater opportunities for young entrepreneurs to do business by building start-ups. Even though the pandemic is almost over, it is believed that the massive use of digital media will not decrease. This study aims to analyze the role of start-ups for the development of student entrepreneurship after the COVID-19 pandemic in Indonesia. The research was conducted with a descriptive qualitative approach. The data was obtained through observation and searching on various digital media platforms and official websites related to student entrepreneurship. The results showed that the role of start-ups during the pandemic for the development of student entrepreneurship was very beneficial, due to the assistance of various platforms or media that could be used to develop the business of student entrepreneurs. Thus, the role of start-ups is the main factor, it is important that these business ideas arise from problems that have been experienced by the Indonesian people, so that from these problems emerge creative solutions so that they are developed by startup business people into a value that can help solve problems and also meet community needs